Cash flow, investment, and investment opportunities: New tests using UK panel data - Carpenter, Robert E.; Guariglia, Alessandra (Journal of Banking & Finance, 2008)
The interpretation of the correlation between cash flow and investment is controversial. Some argue that it is caused by financial constraints, others by the correlation between cash flow and investment opportunities that are not properly measured by Tobin’s Q. This paper uses UK firms’ contracted capital expenditure to capture information about opportunities available only to insiders and thus not included in Q. When this variable is added to investment regressions, the explanatory power of cash flow falls for large firms, but remains unchanged for small firms. This suggests that the significance of cash flow stems from its role in capturing the effects of credit frictions.